COMPARATIVE ANALYSIS OF CERTAIN MICRONUTRIENTS OF PLANTS OF THE SUAEDA GENUS - Ikhsanov Yerbol Saginovich; Litvinenko Yuliya Alekseevna; Seitimova Gulnaz Absattarovna; Burasheva Gauhar Shahmanovna (Academic Scientific Journal of Chemistry, 2019)
The article presents a comparative analysis of the content of some biologically active micronutrients, namely ascorbic acid, retinol and tocopherol in 6 six representatives of the genus Suaeda of the Amaranthaceae family. In this paper, we study the micronutrients of the aerial parts of plants of the genus Suaeda:Suaeda acuminata, Suaeda microphylla, Suaeda altissima, Suaeda spicata, Suaeda vera, Suaeda splendens. Species of Suaeda spicata, Suaeda vera harvested in the province of Lliedia, Spain. Types of Suaeda acuminata, Suaeda microphylla, Suaeda altissima, Suaeda splendens in Ili district, Almaty region As a result, it was established that in all studied objects, tocopherol is present in the largest quantity (from 10 to 16 mg per 100 g). The amount of ascorbic acid varies in the range of 3.2-4.5 mg per 100g. The content of retinol in 6 studied species ranges from 1.7 to 3.0 mg per 100g. The highest content of tocopherol is found in the aerial part of Suaeda microphylla - 16 mg per 100g. Ascorbic acid is also found in the greatest amount in the aerial part of Suaeda microphylla - 4.5 mg per 100g. Retinol is found in the greatest amount in the aerial part of the species Suaeda acuminate - 3.0 mg per 100g.